2024
DOI: 10.1126/sciadv.adl2238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the metaphyseal skeletal stem cell building trabecular bone

Guan Yang,
Qi He,
Xiaoxiao Guo
et al.

Abstract: Skeletal stem cells (SSCs) that are capable of self-renewal and multipotent differentiation contribute to bone development and homeostasis. Several populations of SSCs at different skeletal sites have been reported. Here, we identify a metaphyseal SSC (mpSSC) population whose transcriptional landscape is distinct from other bone mesenchymal stromal cells (BMSCs). These mpSSCs are marked by Sstr2 or Pdgfrb + Kitl − , located just underneath the growth plate, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…31 Recent studies reported LIFR + PDGFRB + CD45 − CD31 − CD235a − MSCs and Pdgfra + Lepr + marrow-associated skeletal stem and progenitor cells could serve as the identification marker of BMSCs in vivo. 32,33 BMSCs exhibit characteristics such as colony-forming ability, self-renewal capacity, and multilineage differentiation potential along mesodermal lineages, enabling the development of various tissues and organs, including bone, AC, and adipose tissue, etc. 33,34 Currently, BMSCs serve as primary cell sources for endogenous AC and OC tissue repair.…”
Section: Cell Sources For Endogenous Ac and Oc Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Recent studies reported LIFR + PDGFRB + CD45 − CD31 − CD235a − MSCs and Pdgfra + Lepr + marrow-associated skeletal stem and progenitor cells could serve as the identification marker of BMSCs in vivo. 32,33 BMSCs exhibit characteristics such as colony-forming ability, self-renewal capacity, and multilineage differentiation potential along mesodermal lineages, enabling the development of various tissues and organs, including bone, AC, and adipose tissue, etc. 33,34 Currently, BMSCs serve as primary cell sources for endogenous AC and OC tissue repair.…”
Section: Cell Sources For Endogenous Ac and Oc Tissue Engineeringmentioning
confidence: 99%
“…The BMSCs are primarily located within the bone marrow and exhibit positive expression of typical cell surface markers, including CD29, CD44, CD73, CD90, CD105, CD146, and CD271. , Conversely, BMSCs typically exhibit negative expression of common cell surface markers, including CD45, CD34, CD14, CD11b, and CD19 . Recent studies reported LIFR + PDGFRB + CD45 – CD31 – CD235a – MSCs and Pdgfra + Lepr + marrow-associated skeletal stem and progenitor cells could serve as the identification marker of BMSCs in vivo. , BMSCs exhibit characteristics such as colony-forming ability, self-renewal capacity, and multilineage differentiation potential along mesodermal lineages, enabling the development of various tissues and organs, including bone, AC, and adipose tissue, etc. , Currently, BMSCs serve as primary cell sources for endogenous AC and OC tissue repair. However, their application is associated with an increased tendency for fibrocartilage formation and ectopic ossification, possibly due to their inherent high osteogenic potential. , Furthermore, in cases of partial-thickness and full-thickness AC injuries where the subchondral bone remains intact, additional procedures such as MF or subchondral drilling are necessary to access endogenous BMSCs .…”
Section: Cell Sources For Endogenous Ac and Oc Tissue Engineeringmentioning
confidence: 99%